A new four-dimensional two-scroll hyperchaos dynamical system with no rest point, bifurcation analysis, multi-stability, circuit simulation and FPGA design. (19th June 2020) - Vaidyanathan, Sundarapandian; Tlelo-Cuautle, Esteban; Sambas, Aceng; Dolvis, Leutcho Gervais; Guillén-Fernández, Omar
This paper deals with the design of a new four-dimensional two-scroll hyperchaos dynamical system with three quadratic non-linear terms. The new two-scroll dynamical system does not possess any rest point suggesting the existence of hidden attractor. This paper provides a detailed analysis such as multistability, symmetry, coexisting hyperchaos attractors and bifurcation properties of the new hyperchaos dynamical system with two-scroll hidden attractor. We realise the dynamic equations of the two-scroll hyperchaos system with an electronic MultiSim circuit. Next, we build, design and implement the two-scroll hyperchaos system on FPGA.